3D comparison of dental arch stability in patients with and without cleft lip and palate after orthodontic/rehabilitative treatment (Journal of Applied Oral Science, 2022)
This study aimed to compare the linear dimensions of the dental arches of adult patients with complete unilateral cleft lip and palate (UCLP) after orthodontic and prosthetic treatment with fixed partial dentures (FPD) to patients without clefts, using 3D technology. This retrospective longitudinal study sample consisted of 35 subjects divided into two groups. Included in this sample were 15 complete UCLP individuals who had received orthodontic treatment before rehabilitation with a fixed partial denture (FG), as well as 20 patients without cleft as control group (CG). All patients were aged between 18 and 30 years. Digital dental casts were obtained in two stages: (T1) end of orthodontic treatment and (T2) one year after prosthetic rehabilitation (FG); and (T1) end of orthodontic treatment and (T2) one year after removal of the orthodontic appliance (CG). Intercanine, interfirst premolar and intermolar distances, and incisor-molar length were obtained. A precalibrated and trained examiner performed the assessments. Intergroup differences between T2 and T1 were compared between the groups using the t test or Mann-Whitney test with a significance level of 5% (p<0.05). The intercanine distance variation (T2-T1) showed statistical difference (p=0.005) increasing in the FG group and decreasing in the CG group. In the interfirst premolar distance variation, FG decreased, while CG increased with statistically significant difference (p=0.008). The intercanine distance of individuals with cleft showed stability, while that of the CG had no stability. The CG showed stability in the interfirst premolar distance, while FG had no stability. These findings showed that the FPD is capable of restricting orthodontic results, leading to a stabilization of the dental arches.